Substitutions of parts of speech in armenian translation of V. Pikul’s novel “The Favorite” - Tsaturyan, Lilit (Bulletin of Yerevan University B: Philology, 2022)
Various transformations are inevitable in any translation. They may be due to linguistic or extra-linguistic aspects. Linguists conditionally divide these transformations into groups taking into account different principles of classification. They are broadly represented at the lexical and grammatical levels. The substitution of parts of speech occupies a large place in grammatical transformations. In the process of translation the substitution of one part of speech of the original language with another is mainly conditioned by grammatical and stylistic features and patterns of the target language.